A multivariate study of the digital divide and digital exclusion - C. Serrano-Cinca; J.F. Mu\~noz-Soro; I. Brusca-Alijarde (International Telecommunications Society (ITS), 2015)
This paper explores the use of Internet, including social networks, e-government services and e-commerce from the perspective of the digital divide. First, it aims to find out what factors explain the digital divide, considered as a multidimensional concept. Second, the article aims to identify the groups that are digitally excluded. The paper is based on survey data (N=2,304) collected in Spain that are analyzed by using multiple regression, principal component analysis and cluster analysis. Two dimensions are identified: the first is the comprehensive use of Internet and the second is the nature of this use, differentiating between a professional use and a recreational and social use of Internet. The paper verifies that factors explaining the digital divide are age, education level, and income. Many unemployed are among the most frequent users of Internet. The most serious problem is encountered in homeworkers, who are mainly woman. NEETs (Not in Education, Employment, or Training) are frequent users of Internet but they only use it for entertainment and to certain extent they are digitally excluded.
Keywords: 330; Digital divide; digital exclusion; e-government; social networks; e-commerce